Building Sustainable Tourism and Strengthening Local Economies in Tourism Villages Through Homestay and Stakeholder Participation - Wayan Suardana; Puput Puji Astuti; Risman Jaya; Muhammad Taufik (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This paper explores the role of diverse stakeholders in the sustainable development of homestays, emphasizing the critical importance of collaboration among various actors to achieve long-term success. Local governments play a crucial role by creating supportive regulations, providing essential infrastructure, and offering training for homestay operators on sustainable practices that can improve service quality and environmental responsibility. Homestay managers are essential for delivering quality services and implementing eco-friendly operations, such as effective waste management and energy conservation. Community involvement is equally vital, as residents can engage in managing homestays and offering local products, thereby ensuring that economic benefits reach a broader segment of the community. Additionally, tourism industry players, including travel agents, promote homestays to a larger audience, while NGOs contribute by educating communities about sustainable tourism practices and advocating for supportive policies. The findings suggest that a collaborative approach among stakeholders is essential for successful and sustainable homestay development, ultimately benefiting local economies and preserving the environment.